KOMPUTERISASI PERHITUNGAN TEBAL LAPIS TAMBAH PERKERASAN JALAN MENGGUNAKAN METODA AASHTO’93 - Siegfried Siegfried (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
At the time most of overlay design methods use the deflection data which are collected through Falling Weight Deflectometer (FWD). Some methods that using this type of data are namely Austroad, AASHTO’93, and many others. The AASHTO’93 method applies some iterative procedure. In order to make the calculation much faster a program of Visual Basic has been performed. Using this program, some advantages can be reached i.e. variation of cumulative standard axles and thickness of overlays required, prediction of remaining life, and also avoiding the human error during calculation process.